A two-phase olive mill by-product (pâté) as a convenient source of phenolic compounds: Content, stability, and antiaging properties in cultured human fibroblasts. (January 2018) - Cecchi, Lorenzo; Bellumori, Maria; Cipriani, Caterina; Mocali, Alessandra; Innocenti, Marzia; Mulinacci, Nadia; Giovannelli, Lisa
Highlights: The two-phase olive mill by-product pâté is a suitable source of phenolic compounds. Dried pâté is a homogeneous powder stable for at least four months. An alcoholic pâté extract proved to have antiaging activity in cultured human cells. 1 g of pâté can provide the same daily intake of about 200 g of a good quality EVOO. Abstract: Pâté is a new olive mill by-product potentially suitable for human consumption. This work aimed to characterize the phenolic profile of pâté samples from four crop seasons (2013–2016) in fresh, dried and stored samples, applying HPLC-DAD-MS-TOF, and to evaluate the antiaging effect in a cell senescence model. The dried pâté contains high levels of hydroxytyrosol, oleuropein derivatives and other phenolic compounds and is stable for several months. A diluted hydroalcoholic extract showed antiaging effects in vitro, comparable to those of pure hydroxytyrosol. Pâté can thus be proposed as an additional economical and environment-friendly source of olive bioactive phenolic compounds, particularly hydroxytyrosol: 1 g of pâté provides a daily intake comparable to that derived from 200 g of a typical virgin olive oil. This work lays the basis for a possible use of this food by-product as a natural ingredient for innovative foods or food supplements, contributing to a healthier lifestyle.